Evaluation of Sexual Abuse and Sexual Assault Cases Which Were Referred to Pamukkale University Faculty of Medicine Department Between 2010 and 2016 - Yazar, Mustafa Eray; Boz, Bora (The Bulletin of Legal Medicine, 2019)
Objective:Sexual crimes are considered to be one of the most serious crimes among human crimes, which can be seen in all societies, since the existence of humanity regardless of the culture, religious belief, socioeconomic level and regime difference. Studies in our country and in many countries show that high number of sexual crimes has been committed. With the fact that the reported cases are less than half of the total, according to various studies, the seriousness of the problem is obvious. Especially in our country, this problem is intensely affected by the sociological changes experienced in recent years. Materials and Methods:In this study, 565 cases of sexual abuse and sexual assault who were referred to Pamukkale University Faculty of Medicine between 2010 and 2016 were examined in terms of sociodemographic characteristics, risk factors and prevention methods.Results:Of the cases, 85.1% (n: 481) were female, 14.9% (n: 84) were male, and 40% (n: 226) were in the 15-18 age group; where 88.1% (n: 498) of the accused were mostly the relatives o acquaintances and 99.5% (n: 562) were male. When the cases evaluated in the Forensic Medicine outpatient clinic were examined (n: 267); it was observed that 11.2% (n: 30) of the cases were evaluated within the first 72 hours after the event and 50% (n: 15) of them were admitted to the state hospital first. In 12.6% of the cases (n: 71), the use of internet-social media was found to be the way of contact for the accused to ...
Keywords: Crime; criminology; sexual abuse; sexual assault